2022
DOI: 10.1080/21655979.2022.2038434
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram/Copper induces antitumor activity against gastric cancer via the ROS/MAPK and NPL4 pathways

Abstract: Disulfiram (DSF) is an anti-alcoholism medication with superior antitumor activity and clinical safety; its antitumor mechanisms in gastric cancer (GC) have not been fully explored. In the present work, low nontoxic concentrations of copper (Cu) ions substantially enhanced DSF’s antitumor activity, inhibiting the proliferation and growth of GC cell lines. DSF/Cu elevated the generation of reactive oxygen species (ROS), and apoptosis was induced in an ROS-dependent manner. This process might involve primary inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…Some studies have shown that Chinese patent medicines and plant extracts can also induce apoptosis through ferroptosis and cuproptosis. Liu et al (2022) found that disulfiram (DSF)/Cu elevated the generation of reactive oxygen species (ROS), and apoptosis was induced in a ROS-dependent manner. Song et al (2022) showed that Yiqi Huayu decoction can induce ferroptosis in GC by affecting the JAK2-STAT3 pathway and the expression of ACSL4.…”
Section: Figurementioning
confidence: 99%
“…Some studies have shown that Chinese patent medicines and plant extracts can also induce apoptosis through ferroptosis and cuproptosis. Liu et al (2022) found that disulfiram (DSF)/Cu elevated the generation of reactive oxygen species (ROS), and apoptosis was induced in a ROS-dependent manner. Song et al (2022) showed that Yiqi Huayu decoction can induce ferroptosis in GC by affecting the JAK2-STAT3 pathway and the expression of ACSL4.…”
Section: Figurementioning
confidence: 99%
“…For example, DSF/Cu complex exhibited antitumor activity against GC cells via modulating the stress response, glycolysis, S6K1, c-Myc and Wnt/β-catenin signaling ( 67 , 68 ). DSF/Cu also induced apoptosis through reactive oxygen species (ROS)/mitogen-activated protein kinase pathway ( 69 ). However, the role of cuproptosis in GC remains unknown, and the evaluation of prognostic value of CRGs has never been conducted in GC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, copper-associated anti-tumor therapies were reported in several cancers, including gastric cancer (22), colorectal cancer (23,24), and lung cancer (25). Therefore, copper ionophore treatment is possible to be a novel therapy for tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, copper chelation RPTDH/R848 nanoparticles were synthesized and applied as a therapeutic agent against metastatic BC via a combination of immune activation and anti-angiogenesis ( 21 ). In addition, copper- associated anti-tumor therapies were reported in several cancers, including gastric cancer ( 22 ), colorectal cancer ( 23 , 24 ), and lung cancer ( 25 ). Therefore, copper ionophore treatment is possible to be a novel therapy for tumors.…”
Section: Discussionmentioning
confidence: 99%